Peningkatan Literasi Sains Menggunakan Media Berbasis Augumented Reality pada Materi Usaha dan Energi Siswa SMPN 17 Banda Aceh - vavilaya, Savira atmaja; Azzarkasyi, Muhammad; Rizal, Syamsul (Journal of Technology and Literacy in Education, 2024)
The rapid development of technology, especially in the field of education, has brought significant changes in the way the teaching and learning process is conducted. One promising technology is Augmented Reality (AR), which can combine the real world with virtual elements to create an interactive and immersive learning experience. In the context of science education, Augmented Reality (AR) has great potential in improving students’ science literacy, particularly in the topics of work and energy, which are often considered difficult to understand due to their abstract nature. This study aims to explore the effectiveness of using Augmented Reality (AR)-based media in enhancing students’ science literacy on the topic of work and energy at SMPN 17 Banda Aceh. The study also examines students’ responses to the use of Augmented Reality (AR) technology in learning. The results of this research are expected to contribute to efforts to improve the quality of science education in schools by utilizing more modern technology, as well as provide insights for teachers and educational institutions in developing technology-based learning strategies.